Перспективы и возможности несеребряной фотографии - Акимов И. А. Игорь Александрович; Барачевский В. А. Валерий Александрович; Гущо Ю. П. Юрий Петрович; Картужанский А. Л. Александр Львович; Томилин М. Г. Максим Георгиевич; Холманский А. С. Александр Сергеевич; Шварц К. К. Курт Куртович; Шеберстов В. И. Валентин Иосифович; Картужанский А. Л. (Ленинград, Химия, 1988)
Авт. указаны на обороте тит. л.